Therapeutic effect analysis on the treatment of congenital glaucoma through modified combined trabeculotomy-trabeculectomy - Zhen-Kai Wu (International Journal of Ophthalmology, 2016)
AIM: To evaluate the therapeutic effect and the safety of the treatment of congenital glaucoma through modified combined trabeculotomy-trabeculectomy. METHODS: The clinical data of 27 cases (altogether 42 eyes), which included 7 cases of infants (10 eyes) and 20 cases of teenagers (32 eyes), of congenital glaucoma undertook modified combined trabeculotomy-trabeculectomy were analyzed retrospectively. The parameters evaluated included the post operation visual acuity, the anterior chamber, the filtering bleb, the intraocular pressure, the C/D ratio, visual field, the retinal nerve fiber layer changes and the complications. RESULTS: The follow-up period was 1 to 29mo, averaging 13.3±7.7mo. Upon the last visit after the operation, functional filtering blebs developed in all the involved eyes. The intraocular pressure was controlled under 21 mm Hg, which was decreased by 60% when compared with that before the operation, without using any medication. There were no significant changes in the post operation visual acuity and the retinal nerve fiber layer thickness before and after the operation in teenager group (P＞0.05), and both the post operation C/D ratio and the visual field mean defect (MD) were reduced compared with those before the operation (P<0.05). There were no severe complications in any of the patients. CONCLUSION: The modified combined trabeculotomy-trabeculectomy can effectively reduce the intraocular pressure and control the development of glaucoma in cases of congenital glaucoma. It is a safe and effective operative method for the treatment of congenital glaucoma.